Moderating Factors Associated With Interrupting the Transmission of Domestic Violence Among Adolescents - Genç, Emel (Journal of interpersonal violence, 2021)
Exposure to child maltreatment in the family-of-origin has consistently been linked to intimate partner violence (IPV) perpetration in adulthood. Although the concept of a cycle of violence presumes that the transmission of violence is expressed directly across generations, some protective factors such as social support, self-esteem, and relationship quality with parents may ultimately be influential in nonviolent behavior in adult relationships. Using the National Longitudinal Study of Adolescent Health data set, we tested protective factors to see if and to what extent they disrupted the association from early childhood maltreatment to experiencing violence later on in adult relationships. We found that there was a positive association between adolescence exposure to maltreatment and adult perpetration and victimization of IPV. Also, social support in adolescence was identified as a predictor of lower levels of violence in adult relationship. Clinical implications were discussed to help therapists intervene with adolescents in the hopes of reducing their propensity toward violent relationships in adulthood.